CONGREGANTS’ PERCEPTIONS OF THE MOSQUE LIBRARY AS A CENTER OF ISLAMIC LITERACY - Nasrullah, Nasrullah; Tawakkal, Tawakkal; Muliyadi, Irvan; Mathar, Muh. Quraisy; Jamin, Jashira; Rodin, Rhoni (Al-Qalam, 2025)
This study investigates congregants’ perceptions of the presence and function of mosque libraries and examines the factors that influence their effectiveness as centers of Islamic literacy. A qualitative research design was employed in three major mosques in South Sulawesi: the 99 Domes Asmaul Husna Mosque in Makassar, the Syekh Yusuf Lakiung Mosque in Gowa, and the Grand Mosque of Maros. Data were collected through observation, in-depth interviews with eight purposively selected participants, and analysis of library management documentation. The findings reveal that although congregants generally demonstrate strong awareness of mosque libraries, their actual engagement with these facilities remains limited. Some view the library as an important source of religious knowledge, while others rely more heavily on oral learning through sermons. Several factors were identified as barriers to optimal use, including limited accessibility, lack of promotion, unattractive physical environments, and outdated collections. In addition, the absence of qualified librarians hinders effective management and the sustainability of literacy programs. The implications of this study suggest that mosque library management should focus on strengthening community outreach, improving facilities and services, regularly updating collections, and integrating digital resources to attract younger audiences. Overall, the findings highlight the untapped potential of mosque libraries as community-based centers of Islamic literacy that can foster lifelong religious learning, promote a culture of reading among Muslims, and enhance the mosque’s educational and social roles within society.